Case report: dengue fever associated acute macular neuroretinopathy - Wang, How-Chen; Lin, Chia-Ching; Chang, Chia-Hsin; Tsai, Jih-Jin (Frontiers in Medicine, 2024)
Dengue fever (DF), caused by the Dengue virus (DENV) and transmitted through Aedes mosquitoes, is well recognized for its systemic manifestations, with its ocular involvement gaining recent attention. We present a case of a 41-year-old Taiwanese female who developed acute macular neuroretinopathy (AMN) following a DF diagnosis related to DENV-1, emphasizing the need for awareness of this complication. The patient, with a history of completely resolved optic neuritis (ON) and comorbidities, experienced blurred vision on day ten after DF onset. The ophthalmic examination revealed macular edema, ellipsoid zone (EZ) infiltration, and choriocapillaris involvement. Despite pulse therapy with corticosteroids, visual disturbances persisted, highlighting the challenge of managing ocular complications. Ocular manifestations in DF include hemorrhages, inflammation, and vascular complications. DF-associated AMN, a rare presentation, poses challenges in diagnosis and treatment response evaluation. While most patients recover spontaneously, some face persistent visual impairment, especially with AMN. Our case underscores the importance of recognizing ocular complications in DF, necessitating a multidisciplinary approach for optimal management and further research to delineate treatment strategies and outcomes.